Vestibular and Ocular Motor Properties in Lateral Medullary Stroke Critically Depend on the Level of the Medullary Lesion - Lee, Seung-Han; Kim, Jae-Myung; Schuknecht, Bernhard; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2020)
Background: Lateral medullary stroke (LMS) results in a characteristic pattern of brainstem signs including ocular motor and vestibular deficits. Thus, an impaired angular vestibulo-ocular reflex (aVOR) may be found if the vestibular nuclei are affected. Objective: We aimed to characterize the frequency and pattern of vestibular and ocular-motor deficits in patients with LMS. Methods: Patients with MR-confirmed acute/subacute unilateral LMS from a stroke registry were included and a bedside neuro-otological examination was performed. Video-oculography and video-based head-impulse testing (vHIT) was obtained and semicircular canal function was determined. The lesion location/extension as seen on MRI was rated and involvement of the vestibular nuclei was judged. Results: Seventeen patients with LMS (age = 59.4 ± 14.3 years) were included. All patients had positive H.I.N.T.S. vHIT showed mild-to-moderate aVOR impairments in three patients (ipsilesional = 1; ipsilesional and contralesional = 1; contralesional = 1). Spontaneous nystagmus (n = 10/15 patients) was more often beating contralesionally than ipsilesionally (6 vs. 3) and was accompanied by upbeat nystagmus in four patients. Head-shaking nystagmus was noted in seven subjects, ipsilesionally beating in six and down-beating in one. On brain MRI, damage of the most caudal parts of the medial and/or inferior vestibular nucleus was noted in 13 patients. Only those two patients with lesions affecting the rostral medulla oblongata demonstrated an ipsilaterally impaired aVOR. Conclusions: While subtle ocular motor signs pointed to damage of the central–vestibular pathways in all 17 patients, aVOR deficits were infrequent, restricted to those patients with rostral medullary lesions and, if present, mild to moderate only. This can be explained by lesions located too far caudally and too far ventrally to substantially affect the vestibular nuclei.